Repensando la relación entre los cambios sociales y los cambios legales en el buenos aires del siglo XIX - M. Shumway, Jeffrey (Revista de Historia Social y de las Mentalidades, 2025)
This study examines connections between court cases of family conflicts in nineteenth-century Buenos Aires and the world of jurisprudence. Although many colonial laws continued inplace after independence, the attitudes of many judges’, lawyers’, and politicians’ toward those laws changed. The result was a shift in interpretation and application of the old laws, a shift that affected the daily lives of many porteños during the nation-building process.